Regrouping of the 3rd Polish Riflemen Division from Jelnia to Żłobin in February 1918 - Jarno, Witold (Armia kontra natura, 2020)
The article describes a little-known episode from the history of Polish military formations in Russia during the First World War. It was the march of the 3rd Polish Riflemen Division in February 1918 from Jelnia (near Smolensk) to Żłobin, where was concentrating the First Polish Corps, commanded by general Józef Dowbor Muśnicki. The march of the 3rd Polish Riflemen Division was unique in the history of the Polish Army, because it took place in very difficult weather conditions – through snowdrifts and in frost reaching 30 degrees at night. Division soldiers marched through territories inhabited by hostile people – fighting constantly with Bolshevik troops, who tried to stop and disarm the Polish division. Her soldiers fought numerous fights with the enemy, including the biggest and bloodiest battle at Pobołów. In almost three weeks, soldiers of the 3rd Polish Riflemen Division went over 400 km, reaching the Żłobin region at the end of February. Here they joined with the First Polish Corps in Russia – ending their epic, which was a proof of the great dedication of the Polish soldier to his homeland.